The Long-Run Consumption Effects of Earnings Shocks - Stephens, Melvin (The Review of Economics and Statistics, 2001)
Although prior studies of job displacement and disability have measured the impact of these shocks in terms of lost earnings, no previous research has linked these permanent earnings shocks to the long-run consumption smoothing behavior of these households. Because consumption is generally considered a better measure of well-being than is income, understanding the link between these earnings shocks and consumption is important in trying to gauge the magnitude of the long-run impact caused by such events. Using the Panel Study of Income Dynamics, the analysis finds the percentage change in consumption is generally less than that of the head's earnings and total family income, especially at the time of the shock. The results also indicate that displaced households respond to an increase in the probability of future job losses by reducing their consumption prior to a job loss. These results suggest that only focusing on earnings overestimates the impact of these shocks on household well-being.